Synergistic effect of ultrasound and reinforced electrical environment by bioinspired periosteum for enhanced osteogenesis via immunomodulation of macrophage polarization through Piezo1 - Jiang, Ting (2024)
The periosteum plays a vital role in repairing bone defects. Researchers have demonstrated the existence of electrical potential in the periosteum and native bone, indicating that electrical signals are essential for functional bone regeneration. However, the clinical use of external electrical treatments has been limited due to their inconvenience and inefficacy. As an alternative, low-intensity pulsed ultrasound (LIPUS) is a noninvasive form of physical therapy that enhances bone regeneration. Furthermore, the wireless activation of piezoelectric biomaterials through ultrasound stimulation would generate electric charges precisely at the defect area, compensating for the insufficiency of external electrical stimulation and potentially promoting bone regeneration through the synergistic effect of mechanical and electrical stimulation. However, the optimal integration of LIPUS with an appropriate piezoelectric periosteum is yet to be explored. Herein, the BaTiO3/multiwalled-carbon nanotubes/collagen (BMC) membranes have been fabricated, possessing physicochemical properties including improved surface hydrophilicity, enhanced mechanical performance, ideal piezoelectricity, and outstanding biocompatibility, all of which are conducive to bone regeneration. When combined with LIPUS, the endogenous electrical microenvironment of native bone was recreated. After that, the wireless-generated electrical signals, along with the mechanical signals induced by LIPUS, were transferred to macrophages and activated Ca2+ influx through Piezo1. Ultimately, the regenerative effect of the BMC membrane with LIPUS stimulation (BMC + L) was confirmed in a mouse cranial defect model. Together, this research presents a co-engineering strategy that involves fabricating a novel biomimetic periosteum and utilizing the synergistic effect of ultrasound to enhance bone regeneration, which is achieved through the reinforcement of the electrical environment and the immunomodulation of macrophage polarization.